Can recreational ecosystem services be inferred by integrating non-parametric scale estimators within a modelling framework? The birdwatching potential index as a case study. (August 2019) - Santos, Mário; Carvalho, Diogo; Luis, Antonio; Bastos, Rita; Hughes, Samantha Jane; Cabral, João Alexandre
Graphical abstract: Highlights: Recreational ecosystem services (RES) assessment support ecosystem management. The novel birdwatching potential index (BWaPz) gauges hotspot attractiveness status. Non-parametric scale estimators support BWaPz robustness for distribution-free data. Hybrid modelling framework (HMF) outputs estimate seasonal changes influencing BWaPz. The integration of BWaPz in HMF was considered useful and generalizable to other RES. Abstract: The ecosystem services approach represents an important and still evolving concept that has the potential to redefine perspectives in ecosystem management by linking different scientific areas within a common framework. Birdwatching is a recreational ecosystem service whose importance has grown in recent years, providing support for rural economies and community-based conservation. Therefore, there is a need for a comprehensive understanding of this ecosystem service dynamics under realistic scenarios of environmental change. We propose the birdwatching potential index, an original approach supported on non-parametric robust scale estimators to assess change in attractiveness of birdwatching hotspots. A demonstrative case study is described, integrating the index within a hybrid modelling framework and testing its performance in dissimilar dynamic scenarios. Contrasting environmental conditions resulted in divergences in the birdwatching potential index and concomitant recreational ecosystem services delivered. The framework simulations also provided information that was considered useful for guiding local conservation actions and management practices to upsurge birdwatchers' interest for a specific hotspot.